Managed aquifer recharge experiences with shallow wells: first analysis of the experimental activities in the high Vicenza plain (Northern Italy) - Altissimo, Lorenzo; Bertoldo, Silvia; Campagnolo, Francesca; Gusmaroli, Giancarlo; Muraro, Teresa; Sottani, Andrea (Acque Sotterranee - Italian Journal of Groundwater, 2014)
In recent decades, groundwater resources of the high Vicenza plain were subjected to an increasing extraction rate and, at the same time, to a lower quantity of groundwater recharge. The result is a decreasing flow from the plain springs and a high reduction in piezometric levels of the middle and lower Venetian aquifers. In order to restore the balance of groundwater resources in the Vicenza area, the Vicenza Province has promoted experimental activities aimed to increase the recharge of the aquifer in the high Vicenza plain and in the River Agno valley, using infiltration wells, forested infiltration areas, infiltration trenches, subsurface fields and infiltration canals. All recharge plants are fed by irrigation water, managed by agricultural consortia only during periods of water surplus. Construction works were preceded by specific geological and hydrogeological investigations to verify the suitability for recharge, with the purpose of optimizing the available economic resources. For the protection of the aquifer system, a chemical background of infiltration water was assessed with periodical chemical-physical and microbiological surveys. After the activation date, a monthly monitoring program started to verify the quality of both surface and groundwater, collecting samples in monitoring wells downstream the infiltration structures. The input flow rate entering the various systems, monitored by automatic instruments either in the superficial structure and in groundwater, have provided interesting information about the volumes and the quality of water. These scientific experiences appear to be very helpful in case of future applications for other sites, especially during critical hydrologic period.